Changes in peripheral blood mononuclear cell electrical properties in response to viral exposure and vaccination - Krista S. P. Clarke; Alexander T. Stewart; Emma L. Sinclair; Rebecca Lewis; Fatima H. Labeed; Deborah K. Dunn-Walters; Michael Pycraft Hughes (Scientific Reports)
Abstract Viral infection triggers both cellular and systemic responses in vivo. These are sometimes difficult to study since the immune system is subject to constant challenge from multiple pathogens. However, during the COVID-19 pandemic, a unique opportunity arose to measure the body’s immune response during lockdown, when exposure to pathogens from the environment was substantially lower. This allowed measurement of COVID-naïve patients, as well as those who had recovered from COVID-19. The effects of subsequent vaccination and boosters could also be assessed. This offers two advantages; an insight into the humoral response to novel pathogens, and the opportunity to measure the ability of the body to respond to challenge from both new pathogens and those to which exposure had already occurred. In this paper, we used dielectrophoresis (DEP) to analyze the electrophysiological fingerprint of peripheral blood mononuclear cells (PBMCs) from donors who had never had COVID-19, those who had recovered from COVID-19, and those who received first, second, or third vaccine doses. This was performed before and after incubation with the receptor binding domain of the SARS-CoV-2 spike protein to determine whether differential changes in the electrical properties of PBMCs could be detected and evaluated. Clear trends in response over time were observed, suggesting that DEP could pave the way towards a new correlate of protection (CoP) to SARS-CoV-2. Furthermore, since the test measures immune response to challenge, it may be widely applicable to other diseases.